(untitled) (Research, Society and Development, 2022)
School management’s main focus is to assure that institutions are able to successfully carry out their educational role. This article aims to identify the understanding possessed by school manager about Physical Education and how they outline social and educational goals in this context. Qualitative research was based on a semi-structured interview scrip, which was built based on the guiding principles defined by UNESCO for management in Physical Education. Data analysis was performed through IRAMUTEQ software, using ‘‘Word Cloud’’ and ‘’Similatiry Analysis’’ techniques. Results point that the manager assume a supporting role in actions linked to Physical Education in schools, due to a lack of mastery of curricular component specificities. Also, decision centrality falls on teachers, modifying the decision making structure in school’s reality.